The Influence of Oral Hygiene Education on The Oral Health Status of Patients Suffering from HIV/AIDS - Yohanis Lefta; Rosyidah Arafat; Syahrul Syahrul (Indonesian Contemporary Nursing Journal, 2021)
Introduction: Poor oral hygiene and dental care can affect oral intake which results in decreased endurance and increases the risk of opportunistic or systemic infections. Method: The research was carried out the RSUD dr. M. Haulussy Ambon, Maluku, Indonesia, using a quasi-experimental method, involving 30 nurses and 20 patients. The level of knowledge and skills is evaluated before and after oral hygiene education for nurses. Patients were measured with a Beck Oral Assessment Scale (BOAS) score, and C. albicans yeast culture before and after the intervention was given in the form of oral hygiene using a soft toothbrush and dental floss for one week. Result: The influence of oral hygiene education on nurses knowledge with median value of pre-education 36.00 and post-education 91.00 and nurse skills have median value of pre-education 67.00 and post-education 100.00 with a significant value of p = 0.001 <0.05. There is an increase in knowledge and skills after educational activities. Before oral hygiene treatment was applied with a review of the BOAS score it had a median value of 11.00 after the intervention became 6.00 a significant value of p= 0.001<0.05, which showed a decrease in scores after oral hygiene treatment. Examination of C. albicans fungus with a median value of 79.00 pre-intervention and 31.00 at post-intervention, a significant value of p= 0.001, showed a decrease in the number of post-intervention fungi. Conclusion: Nurses should conducted Oral hygiene regularly to improve oral health status of AIDs patiens.